Activités langagières, énonciation et cognitionLa centration sur les apprentissages - Henri Portine (Recherches en didactique des langues et des cultures)
Starting from the notion of language activities (plural) as used in the Common European Framework of Reference (CEFR), the author compares this with the notion of "activité langagière" (singular) as analyzed in "énonciation" and cognition theories. This leads to detection of the "omission" of cognitive processes in the CEFR. The author then distinguishes three theoretical paradigms that he considers essential to the analysis of "activité langagière". A further consideration of "activité langagière" and learning process leads to the conclusion that "activité langagière" and learning activities must be distinguished independently. Finally, his proposal is to associate "pedagogical tasks" with "learning activities" instead of "language activities".